Diagnósticos e intervenções de enfermagem aos pacientes em terapia anticoagulante. - Barbosa, Maria Shirley; Mafei, Francisco Humberto; Marin, Maria José Sanches (FapUNIFESP (SciELO), 2004)
Patients under treatment with oral anticoagulants present specific needs for which nursing care plays an important role, especially to prevent complications. The present review was carried out aiming at discussing nursing diagnoses for these patients by using the system of the North American Nursing Diagnoses Association--NANDA. Diagnoses for such patients depict the risk of bleeding and rethrombosis almost always due to the ineffective control of the therapeutic regimen and the deficit in the volume of fluids during active bleeding. Also, nursing interventions and assessment criteria are proposed for such conditions. The authors see the team's preparation to deal with such therapy as relevant for successful assistance.
Nursing diagnoses and intervention for patients under anticoagulant therapy
Keywords: anticoagulant agent; bleeding; chemically induced disorder; human; nursing; nursing diagnosis; review; Anticoagulants; Hemorrhage; Humans; Nursing Diagnosis